Between the oral and the written. Dialectal elements as exponents of orality in Internet comments - Kucharzyk, Renata (Papers in Linguistics, 2024)
The article aims at analysing Internet comments in the context of the role dialectal elements play in them. A characteristic feature of this Internet genre, situated on the borderline between speech and writing, consists in the occurrence of components representing different varieties of language. Dialectal elements, originating from a primarily oral code, can function in Internet comments as exponents of orality. Their use enhances expressiveness, emotionality and engagement as well as setting the message in a specific context, and thus giving such texts characteristics that are typical of oral culture. The presented study refers to Walter J. Ong’s theory of orality and literacy. He identifies two types of orality: primary and secondary. The former refers to illiterate people, while the latter, associated with electronically mediated communication, is based on knowledge of writing. As the analysis of excerpts from Internet forums shows, the use of dialectal elements reflects, among others, the following features of primary orality: accumulation instead of analysis – which is associated with the use of formulas, reproduction of terms, phrases and sentences in their entirety; redundancy, i.e. the presence of redundant elements in the utterance; and a strong agonistic character, associated with competition and struggle. The material that is the basis for the presented considerations comes from the years 2010–2022.